Crude Oil Option Market Parameters and Their Impact on the Cost of Hedging by Long Strap Strategy - Åamasz, Bartosz; Iwaszczuk, Natalia (International Journal of Energy Economics and Policy, 2019)
This study aims to examine the impact of selected market parameters of the European crude oil options on the hedging costs and break-even points (BEPs) in the Long Strap strategy. The paper analyses the impact of the following market parameters: volatility and the future price of crude oil, the strike price and time to expiration. The theoretical aspect consisted in using the Black model to calculate the value of the option price and the Long Strap strategy BEP in the condition of ever-changing market parameters. These calculations, by determining implied volatilities of the options, have been adapted to the actual data from the exchange market for the options on WTI futures contract. It was made possible owing to the QuikStrike platform made available by a CME Group exchange. To obtain information about the impact of volatility, time and price of futures on the costs of hedging and BEPs in the Long Strap strategy, the authors calculated the Greeks (delta, gamma, vega and theta) for the crude oil options. Having done that, not only could they determine the direction but also the power of impact that the parameters had on the final results in the Long Strap strategy. Keywords: commodity options, crude oil price risk, Long Strap option strategy JEL Classifications: G13, G32 DOI: https://doi.org/10.32479/ijeep.8613